Green networking and communications ICT for sustainability - Khan, Shafiullah; Lloret Mauri, Jaime (CRC Press, 2014)
Although the information and communication technology (ICT) industry accounted for only 2 percent of global greenhouse gas emissions in 2007, the explosive increase in data traffic brought about by a rapidly growing user base of more than a billion wireless subscribers is expected to nearly double that number by 2020. It is clear that now is the time to rethink how we design and build our networks. Green Networking and Communications: ICT for Sustainability brings together leading academic and industrial researchers from around the world to discuss emerging developments in energy-efficient netw.
Includes bibliographical references and index
Keywords: Telecommunication -- Energy conservation; Computer networks -- Environmental aspects; Sustainable engineering; Green technology; Télécommunications; Économies d'énergie; Réseaux d'ordinateurs; Aspect de l'environnement; Ingénierie durable; Technologie de protection de l'environnement; TECHNOLOGY & ENGINEERING; Mechanical